GROWTH OF JUVENILE HORSES HOOF CLAMS (Hippopus hippopus) REARED IN COASTAL WATERS, PARI ISLAND, KEPULAUAN SERIBU - Pangabean, L. M.G.L.; Dwiono, S. A.P.; Setyono, D. E. Djoko (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2006)
The main purpose of this present study is to determine the growth and survival rate of juvenile horses hoof clams Hippopus hippopus) and to find out a suitable site for their rearing in nature. Juveniles used in this study were about 3 years old, produced in the hatchery of CV Dinar, Bali. They were reared in the cages, placed on the sea bed at several sites, namely: (1) on the reef flat, (2) on the bed of a lagoon, and (3) on the sea channel. After 360days of rearing, the highest daily growth was found for juveniles reared in site-2, i.e. 0.110 mm in length, 0.080 mm in width and 0.091 mm in height. These values were significantly different from other two sites. The survival rate after 360 days of rearing was 85.5% in site-1, 99.4% in site-2 and 96.8% in site-3. Based on these results the bed of a lagoon is the best and suitable site to grow horses hoof clam juveniles in nature. Water condition at this site is relatively calm with sandy-muddy substrates and relatively dense seagrasses, mainly Thallasia spp.",